Biochemical Evaluation of Two Endangered Medicinal Taxa of Marathwada Region - Wadikar M.S.3, Tambe S.S.1*, Kadam V.B.2 and (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US;">The seasonal variation of protein and amino acid content have been investigated from leaves, wood and bark ofÂ  Madhuca indica and Mimusops elengi. Madhuca indica and Mimusops elengi are the medicinally important plant of Marathwada region. Comparative account of protein contents of leaves, wood and bark of Madhuca indica showed higher level (range 5.57 to 7.74mg/g dry wt.) than Mimusops elengi (range 2.66to 4.93 mg/g dry/wt.).The leaves of Madhuca indica showed high level of amino acid content (range 0.42 to 0.94 mg/g/dry wt.) and wood of Mimusops elengi was lower amino acid content (range 0.41 to 0.88mg/g dry wt.).